Implementasi Limited Tolerance Relation Untuk Sistem Informasi yang Tidak Lengkap Pada Data Mahasiswa - Edi Sutoyo (Universitas Darussalam Gontor, 2018)
Rough set theory is one of the mathematical models for dealing with a vague, imprecise, and fuzzy knowledge that has been successfully used to handle incomplete information systems. Since, in fact in the real-world problems, often found the conditions that are the user can not provide all the necessary preference values. In this research, an implementation of extension technique of rough set theory that called limited tolerance relation is used to overcome incomplete information systems in student data at Telkom University. Based on the obtained results, the limited tolerance relation technique successfully used to handle that problem. The results show that the technique achieved the accuracy of 96.04% with an execution time of 3.1830 seconds.